2021
DOI: 10.3390/jof7080667
|View full text |Cite
|
Sign up to set email alerts
|

Candida glabrata: Pathogenicity and Resistance Mechanisms for Adaptation and Survival

Abstract: Candida glabrata is a yeast of increasing medical relevance, particularly in critically ill patients. It is the second most isolated Candida species associated with invasive candidiasis (IC) behind C. albicans. The attributed higher incidence is primarily due to an increase in the acquired immunodeficiency syndrome (AIDS) population, cancer, and diabetic patients. The elderly population and the frequent use of indwelling medical devices are also predisposing factors. This work aimed to review various virulence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 111 publications
2
65
0
Order By: Relevance
“…Intriguingly, although these two C. glabrata isolates were recovered from the same site of a patient at a three-day interval after MCF treatment but before VRC treatment and exhibit POS-resistance without functional mutation in ERG11 and PDR1, the different expression patterns of ERG11 and CDR1 further indicate that they are two distinct isolates. Since the two isolates were recovered without triazole exposure, they probably harbor intrinsic POS-resistance, in line with the fact that some C. glabrata isolates have intrinsic resistance to triazoles [38]. On the other hand, studies also demonstrated that prior echinocandin therapy was a risk factor of both echinocandin-resistance and triazoleresistance [39], indicating that the reduced susceptibility to POS may be induced by MCF therapy in the patient.…”
Section: Discussionmentioning
confidence: 73%
“…Intriguingly, although these two C. glabrata isolates were recovered from the same site of a patient at a three-day interval after MCF treatment but before VRC treatment and exhibit POS-resistance without functional mutation in ERG11 and PDR1, the different expression patterns of ERG11 and CDR1 further indicate that they are two distinct isolates. Since the two isolates were recovered without triazole exposure, they probably harbor intrinsic POS-resistance, in line with the fact that some C. glabrata isolates have intrinsic resistance to triazoles [38]. On the other hand, studies also demonstrated that prior echinocandin therapy was a risk factor of both echinocandin-resistance and triazoleresistance [39], indicating that the reduced susceptibility to POS may be induced by MCF therapy in the patient.…”
Section: Discussionmentioning
confidence: 73%
“…C. glabrata is more closely related to S. cerevisiae than to C. albicans [59,134,[136][137][138][139]. It is a major opportunistic human fungal pathogen that has become the second most frequent cause of Candida infections [134,[140][141][142][143]. It is a nondimorphic yeast that exist as small blastoconidia under all environmental conditions as a pathogen (it does not form pseudohyphae at temperatures above 37 • C) [134].…”
Section: Yeasts Expressing Flo Proteins Involved In Human Infectionsmentioning
confidence: 99%
“…C. glabrata can cause superficial and life-threatening dissemination infections reaching high mortalities of around 40% [144]. Immunocompromised, cancer and diabetic patients are particularly susceptible [18,54,142,[145][146][147]. C. glabrata shows a high antifungal resistance against azole antifungal agents [24].…”
Section: Yeasts Expressing Flo Proteins Involved In Human Infectionsmentioning
confidence: 99%
“…Its high mortality rate and its frequent resistance to antifungals make it a pathogen of clinical importance and, therefore, it is essential to know its virulence factors ( Lamoth et al., 2018 ). C. glabrata does not undergo yeast-to-hypha transition as Candida albicans does, yet it has developed other virulence factors such as the production of hydrolytic enzymes (e.g., phospholipases, proteases, and hemolysins), the ability to evade host defenses, tolerance to high-stress environments, and resistance to neutrophil killing ( Silva et al., 2012 ; Hassan et al., 2021 ). Furthermore, it contains an extraordinarily large repertoire of genes encoding putative GPI-modified cell wall adhesins in its genome conferring the yeast high adhesion and biofilm formation capacity onto host epithelia and abiotic surfaces ( De Groot et al., 2013 ; Xu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%